Prevalence of Cardiac Sarcoidosis in Patients Presenting with Monomorphic Ventricular Tachycardia. Issue 3 (17th September 2013) - NERY, PABLO B.; Mc ARDLE, BRIAN A.; REDPATH, CALUM J.; LEUNG, EUGENE; LEMERY, ROBERT; DEKEMP, ROBERT; YANG, JIM; KEREN, ARIEH; BEANLANDS, ROB S.; BIRNIE, DAVID H.
<x xml:space="preserve">Abstract</x> Introduction Sarcoidosis is a granulomatous disease of unknown etiology, which involves the heart in 5–25% of cases. Although ventricular tachycardia (VT) has been reported as the first presentation of sarcoidosis, its prevalence has not previously been investigated. In this prospective study, we sought to systematically investigate the prevalence of cardiac sarcoidosis (CS) in patients presenting with monomorphic VT (MMVT) and no previous history of sarcoidosis. Methods Consecutive patients presenting with MMVT to a tertiary care center were screened for inclusion. Patients with idiopathic VT, VT secondary to coronary artery disease, or prior diagnosis of sarcoidosis were excluded. Included patients underwent F‐18‐fluorodeoxyglucose positron emission tomography (PET) scan. In subjects with PET scanning suggestive of active myocardial inflammation, histological diagnosis was confirmed through extracardiac or endomyocardial biopsy (EMB). Results A total of 182 patients presented to our institution with VT between February 2010 and September 2012 and 14 subjects met inclusion criteria. Within this group, six of 14 (42%) patients had abnormal PET scans suggesting active myocardial inflammation. Four of the six patients had tissue biopsies that were diagnostic of sarcoidosis; the remaining two patients had guided EMB indicating nonspecific myocarditis. Atrioventricular block was observed in three of four (75%) patients with CS and none in 10 of the others (P = 0.022). Three of the four patients had pulmonary sarcoidosis and one patient had isolated CS. All four patients were treated with corticosteroids. Conclusion In this prospective study, four of 14 (28%) patients presenting with MMVT (without idiopathic VT, ischemic VT, or known sarcoidosis) had CS as the underlying etiology. Clinicians should consider screening for CS in patients with unexplained MMVT.